Quali Coffee Roastery: Asesmen Alienasi Budaya Organisasi Pemanggang Kopi Gelombang Ketiga berbasis Kapitalis/Laba - Buhaira Iza (Mahesa Research Center, 2023)
The “assessment” & “alienation assessment” examination method, which analyzes how gift-exchange values shape the value of a commodity in the capitalist economic mode – focuses on analyzing “gift-giving” patterns that occur within the “supply chain” as well as the relationships between business owners, labor and commodity in the so-called “impersonal and capitalist mode”. Through ethnographic research on the third wave cultured coffee roasting business entity of